Clinical outcomes and urodynamic analysis of microsurgery combined with multilayer fascial tissue coverage for new urethra in the treatment of hypospadias in male children - Zheng, Wei; Guo, Shilei; Shi, Xiaoqing; Wang, Jie; Zhang, Bosong; Li, Liwei; Liu, Chuang; Yang, Bin (Frontiers in Surgery, 2025)
ObjectiveTo compare and analyze differences in the clinical effect and postoperative urodynamic indexes of microsurgery combined with covering new urethra by multilayer fascial tissue coverage tissues and conventional surgery alone in the treatment of male children with hypospadias.MethodsA total of 80 male children with penile hypospadias who were hospitalized in Baoding Hospital, Beijing Children's Hospital Affiliated to Capital Medical University were randomly divided into two groups, with 40 in each group. Children in the study group underwent microsurgery combined with covering new urethra by multilayer fascial tissue coverage tissues, while those in the control group were provided with traditional tubularized incised plate (TIP) urethroplasty alone. Further comparative analysis was performed on the operation effect, operation time, total intraoperative bleeding, postoperative length of stay in the hospital and the incidence of surgical complications between the two groups. All male children were followed up for 6 months to compare and analyze the changes of urodynamic parameters such as maximum urinary flow rate (Qmax), mean urinary flow rate (Qavc), post-void residual urine (PVR) before and after surgery.ResultsThere were statistically significant differences that the operation time (p = 0.03) was longer while the postoperative length of stay in the hospital (p = 0.000) was shorter in the study group than those in the control group. The effective rate of the study group was 97.50%, while that of the control group was 82.50%, with statistically significant difference (p = 0.025). The incidence of surgical complications was 7.50% in the study group and 25.00% in the control group 3 months after operation (p = 0.034). There was statistically significant difference that the HOSE score of the study group was significantly higher than that of the control group (p = 0.000). Meanwhile, there was no significant difference in indicators such as Qmax, Qavc and PVR between the two groups before surgery; while the levels of Qmax and Qavc in the study group were higher than those in the control group 6 months after surgery, with statistically significant difference (p = 0.000).ConclusionMicrosurgery combined with covering new urethra by multilayer fascial tissue coverage tissues has certain clinical value in the treatment of male children with hypospadias, which shows good therapeutic effect, shorter length of stay in the hospital, lower incidence of postoperative complications, and significantly improved urodynamic indicators, despite slightly complicated operation and relatively longer duration of operation.